2015
DOI: 10.1038/nrg3935
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing ancient genomes and epigenomes

Abstract: Research involving ancient DNA (aDNA) has experienced a true technological revolution in recent years through advances in the recovery of aDNA and, particularly, through applications of high-throughput sequencing. Formerly restricted to the analysis of only limited amounts of genetic information, aDNA studies have now progressed to whole-genome sequencing for an increasing number of ancient individuals and extinct species, as well as to epigenomic characterization. Such advances have enabled the sequencing of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
160
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 207 publications
(164 citation statements)
references
References 134 publications
1
160
0
3
Order By: Relevance
“…Recent work based on ancient DNA has revealed that, beyond genomes, ancient genome-wide methylation and nucleosome maps can be reconstructed using patterns of DNA degradation along the genome (Gokhman et al 2014(Gokhman et al , 2016Orlando and Willerslev 2014;Orlando et al 2015;Pedersen et al 2014). Combined with current efforts of the FAANG consortium , such approaches promise to reveal the true extent of past individual plasticity and how patterns of gene regulation were modified in response to new domestication/selection targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work based on ancient DNA has revealed that, beyond genomes, ancient genome-wide methylation and nucleosome maps can be reconstructed using patterns of DNA degradation along the genome (Gokhman et al 2014(Gokhman et al , 2016Orlando and Willerslev 2014;Orlando et al 2015;Pedersen et al 2014). Combined with current efforts of the FAANG consortium , such approaches promise to reveal the true extent of past individual plasticity and how patterns of gene regulation were modified in response to new domestication/selection targets.…”
Section: Discussionmentioning
confidence: 99%
“…After 30 years, the whole nuclear genome of this species has been characterized to an average coverage of depth of approximately eightfold, which confirmed the close genetic affinities with plains zebras from Southern Africa, while unveiling genomic loci underlying their unique genetic makeup . The development of innovative molecular methods (for a review, see Orlando et al 2015) has clearly facilitated the transition from the characterization of short sequences to whole-genome sequencing, improving our ability (i) to extract ultrashort and damaged DNA fragments from archaeological material (Dabney et al 2013;Gamba et al 2016), (ii) to construct DNA libraries encompassing the whole extract complexity (Meyer et al 2012;Gansauge and Meyer 2013), and (iii) to even preferentially enrich DNA libraries for authentic ancient templates (Carpenter et al 2013;Fu et al 2013;Gansauge and Meyer 2014). However, the main driver of this transition has been the advent of highthroughput DNA sequencing, which considerably increased the sensitivity and reduced both the cost and time related to the analysis of ancient DNA extracts.…”
Section: Predomestication Timesmentioning
confidence: 99%
“…Therefore, all ancient DNA (aDNA) shotgun sequencing projects are metagenomic in nature. While earlier aDNA research has mostly focused on the evolution of animals and plants [2,3], a growing number of studies are now centering on the identification and characterization of ancient pathogens and microbiomes . CC-BY-NC 4.0 International license It is made available under a (which was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
Section: Main Textmentioning
confidence: 99%
“…The scale and speed of these technologies are aiding the analysis of genomes and improving our understanding of proteins and their interaction with nucleic acids. HTS has been applied to varied applications (Table I) from understanding the role of noncoding sequence variants in cancer [7], identifying genomic targets of small molecules [8] to the reconstruction of ancient genomes and epigenomes [9]. [10].…”
Section: Hts Pipeline Applications and Platformsmentioning
confidence: 99%